Answer:
x=3
Explanation:
Note: I am assuming that the “x” is a variable, and not the multiplication sign. Please correct me if I am wrong.
2(0.5x-0.6)=0.6x
Step 1: Simplify both sides of the equation.
2(0.5x)+2(-0.6)=0.6x - According to Distributive Property
x+-1.2=0.6x
x-1.2=0.6x
Step 2: Subtract 0.6x from both sides.
x-1.2-0.6x=0.6x-0.6x
0.4x-1.2=0
Step 3: Add 1.2 to both sides.
0.4x-1.2+1.2=0+1.2
0.4x=1.2
Step 4: Divide both sides by 0.4
![(0.4x)/(0.4)=(1.2)/(0.4)](https://img.qammunity.org/2023/formulas/mathematics/high-school/unm81ku59uiiu7zg6ht2ts2q4mlodnmwdj.png)
x=3